English in Education in Nepal: A Comprehensive Overview - Khadka, Bishnu Kumar (Journal of NELTA Gandaki, 2024)
Education is shaped and directed by the medium of dissemination. It is the language used as the medium of disseminating educational norms and values to the human capital of the nation. In this regard, this article briefly summarises the role and coverage of English in the Nepali education system via curricula of Nepali school to university education. Based on the analysis and interpretation of the review of the related literature and evidence, it was found that the English language has been playing a dominant role in the Nepali education system from school to university level in terms of the medium of teaching and learning, curricula, testing and certification. English serves as the primary language for curricula, textbooks, reference materials, and reading resources mandated for instruction and study across all educational levels in Nepal, starting from nursery through tertiary education. It acts as the medium of instruction in numerous private institutions and certain government-funded public schools. Moreover, it is utilised as the language for conducting final examinations, including the formulation of question papers for most subjects, excluding language-specific courses. In technical fields and some general subjects, it is also used for answering exam questions.